Effect of a lifestyle-focused electronic patient support application on risk factor management in post-myocardial infarction patients – a randomized controlled trial. (25th November 2020) - Ogmundsdottir Michelsen, H; Sjolin, I; Back, M; Gonzalez, M; Olsson, A; Sandberg, C; Schiopu, A; Leosdottir, M
Abstract: Background: Cardiac rehabilitation (CR) is central in reducing morbidity and mortality after myocardial infarction (MI). However, the fulfillment of guideline recommended CR targets is unsatisfactory. eHealth offers new possibilities to improve clinical care. Purpose: The aim of this study was to assess the efficacy of a mobile device application to support adherence to lifestyle advice and self-control of risk factors as a complement to traditional CR after MI. Method: This unblinded multi-centre randomized controlled trial included 150 patients with MI (81% men, 60.4±8.8 years). All patients in the intervention (INT) and control (CON) groups participated in a 1-year CR program. Additionally, INT patients (n=101) received access to the mobile device application for 25 weeks post-MI where information about lifestyle (i.e., diet, physical activity, smoking), modifiable risk factors (i.e., weight, blood pressure (BP)), and symptoms could be registered. The software provided direct positive feedback and lifestyle advice. Data was reviewed twice weekly by the CR nurse. The primary outcome was change in sub-maximal exercise capacity (W) between an exercise test 2-weeks post MI and at follow-up 4 month later. Secondary outcomes included changes in lifestyle and modifiable risk factors including body mass index, waist circumference, blood-lipids, fasting glucose and HbA1c, between baseline and 2-week, 2-month and 1-year follow-up visits. Regression analysis was used, adjusting for relevant baseline variables. Results: Participation in CR was high, with 96% of INT patients and 98% of the CON patients attending the 1-year follow-up visit. Forty-six percent of the INT patients and 57% of the CON patients attended centre-based exercise training (p=0.1). In the INT group 86% logged data in the application at least once. Adherence, defined as logging data at least twice per week, was 92% in week 1 and 57% in week 25. There was a numerical trend toward better exercise capacity improvement in the INT group (INT +14.4±19.0 vs. CON +10.3±16.1 W, p=0.2) although differences were non-significant. INT patients achieved larger BP reduction at 2-weeks (systolic) and 2-months (systolic and diastolic) (Figure). At 2-months 70% vs. 46% of smokers in the INT vs CON groups had quit smoking, and at 1-year the respective percentages were 57% vs. 36%. The number of smokers in the study was however low (n=33) and the differences non-significant. For other secondary endpoints no differences were observed. Conclusion: Complementing CR with a mobile device application improved BP during the first months after MI, and non-significant trends towards better exercise capacity and higher smoking cessation rates were observed. Even though the differences were non-significant in our small study sample, they indicate that using eHealth in the form of a mobile device application could clinically benefit post-MI patients participating in CR. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Governmental funding of clinical research within the National Health Services in Sweden.